Disruptive Leadership in Enhancing Business Performance in Hotel Industry of Thailand: The Mediating Role of Innovation - Chansuchai, Pichamon; Rotjanawasuthorn, Sippaphat; Jermsittiparsert, Kittisak (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at exploring the association among the disruptive leadership, innovation and business performance. In addition, the mediating effect of innovation in the relationship between disruptive leadership and business performance is examined. The study tries to learn how the technological innovation or innovation affects the business performance of an enterprise. The data used in analysis was collected from 288 managers working in hotel industry in Thailand, the study finds empirical backing to support each hypothesis. The disruptive leadership is demonstrated to be a significant antecedent of business performance and innovation. Next, business performance is substantially predicted by innovation. Lastly, the innovation mediates between the association of disruptive leadership and business performance. The study even possessed the practical implications for the hotel managers in Thailand.